Educational Needs and Training for Women Empowerment in India - Mukhtar Ahmed; Mohd Zameer; Sunil Kumar Verman; Sunita Godiyal (TRANSBAHASA, 2021)
Women in India have faced a lot of problems and issues for their rights. Therefore, the present paper aims to examine the role of education for women empowerment in India and study the government schemes for women empowerment in India. The present study is based on the descriptive type of research. For this study, the researcher used secondary data. The study found that women empowerment is an energetic and dynamic process that facilitates them to realize their identity and power in all characteristics. Due to the lack of educational facilities and training, Indian women left their education in the middle. That is why Indian women are far away from their rights. Most of the Indian women are housewives, but in the present time, it has been improved in many areas; most of the vocational courses and training programs have been introduced by the Indian government.